Defining priority areas for conservation based on multispecies functional connectivity - Lamounier, Wanderson Lopes; Santos, Juliana Silveira dos [UNESP]; Rodrigues, Evandro Luís; Drumond, Maria Auxiliadora (Elsevier, 2024)
Habitat fragmentation poses a significant challenge to biodiversity conservation. Well-designed ecological corridors can effectively enhance connectivity between habitat areas, particularly within Protected Areas (PAs), thereby mitigating biodiversity loss. Herein, we proposed a methodological approach for identifying Priority Areas for Conservation (PACs) of biodiversity based on functional connectivity for different species of birds and terrestrial mammals. We applied the proposed methodology in a biodiverse region in Brazil that harbors a mosaic of PAs and remaining areas of natural vegetation under anthropogenic pressure, primarily from mineral extraction activities. We used ecological corridor simulations as input data and a set of geographic information systems tools to delineate the priority areas. In total, we identified 24 priority areas for the conservation of 10 bird and 5 mammal species under different extinction threat levels and preferential habitat types, which varied among seasonal semideciduous forests, savannas, and rupestrian grasslands. The sizes of the priority areas identified ranged from 834.42 to 7954.36 ha. The proposed methodology can be applied to define priority areas for biodiversity conservation at a regional scale for different species or groups of species worldwide.
Keywords: Bird; Ecological corridor; Functional connectivity; Mammal; Multispecies modeling